PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PERUMAHAN UMUM NASIONAL SAMESTA PARAYASA PARUNG PANJANG DI KABUPATEN BOGOR - Nurila Astuti, Nafasya; Haryantini (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the Promotion Variables (X1), Price (X2), Purchasing Decisions (Y), and the Influence of Promotion and Price on Purchasing Decisions at the Samesta Parayasa Parung Panjang National Housing Complex in Bogor Regency. This research method uses a quantitative method with an quantitative descriptive approach and the population in this research is 11,000 consumers. The sample used in this research used the entire population of 99 consumers as respondents. In this research the sampling technique used is probability sampling. The results of the Promotion variable have a significant effect on Purchasing Decisions with a tcount value of 8.553 > ttable 1.660 and a sig. < 0.1 (0.000 < 0.1). The results of the Price variable have a significant effect on Purchasing Decisions with a calculated t of 9,803 > t table of 1.660 and a sig value. < 0.1 (0.000 < 0.1). The results of the Promotion and Price variables simultaneously have a significant influence on Purchasing Decisions with a calculated f value of 69,523 > 2.362 and a sig value < 0.1 (0.000 < 0.1).